'Hope I never stop': older men and their two-wheeled love affairs. Issue 1 (1st January 2017) - Minello, Karla; Nixon, Deborah
ABSTRACT: The purpose of this paper is to explore the meanings and experiences of road cycling to older men, specifically in the context of ageing. Using interpretive phenomenology, we explored the lived experiences of 12 men, aged 52–82 years. The generally middle class, predominantly white men lived in Ontario, Canada. Four interrelated themes – enjoying the bike, the ride, and the self; experiencing camaraderie; being fit and feeling well; and embracing ageing – described the essences of road cycling to these men. We encountered men who were at one with their bikes and discovered cycling to be a multi-layered phenomenon – a physical activity with few limitations to participation and a conduit to exercise and well-being. As does cycling, ageing begins in the physical; cycling offered these men a way to resist and reconceptualize society's tragedy decline discourse of ageing. This study illuminates the lives and experiences of a group of older men, from their perspective. We extend the leisure literature by exploring how some older men resist society's tragedy decline discourse of ageing through road cycling and reconstruct notions of what ageing can mean.